2022
DOI: 10.1002/adhm.202201138
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Production of Wholly Cellular Bioinks via the Optimization of Human Induced Pluripotent Stem Cell Aggregate Culture in Automated Bioreactors

Abstract: Combining the sustainable culture of billions of human cells and the bioprinting of wholly cellular bioinks offers a pathway toward organ-scale tissue engineering. Traditional 2D culture methods are not inherently scalable due to cost, space, and handling constraints. Here, the suspension culture of human induced pluripotent stem cell-derived aggregates (hAs) is optimized using an automated 250 mL stirred tank bioreactor system. Cell yield, aggregate morphology, and pluripotency marker expression are maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…In terms of the physical microenvironment, studies have shown that bioinks containing compacted cellular aggregates exhibit higher yield stress than slurries of individual cells, enabling the printing of more mechanically stable structures. 202 Daly et al developed a bioprinting method in which spheroids could move within a shear-thinning hydrogel, which could self-heal to localize the spheroids. 203 High celldensity microtissues with specific shapes could be formed by directed fusion between spheroids within the hydrogel.…”
Section: D Bioprinting Technologymentioning
confidence: 99%
“…In terms of the physical microenvironment, studies have shown that bioinks containing compacted cellular aggregates exhibit higher yield stress than slurries of individual cells, enabling the printing of more mechanically stable structures. 202 Daly et al developed a bioprinting method in which spheroids could move within a shear-thinning hydrogel, which could self-heal to localize the spheroids. 203 High celldensity microtissues with specific shapes could be formed by directed fusion between spheroids within the hydrogel.…”
Section: D Bioprinting Technologymentioning
confidence: 99%
“…This entirely synthetic vascularization platform thus paves the way for the creation of tissue models of unprecedented complexity and scale. In another instance, Ho et al provided a roadmap for organ-scale tissue engineering by integrating the bioprinting of completely cellular bioinks with the development of billions of human cells [128]. Using a stirred tank bioreactor technique, the cultivation of hiPSC-derived aggregates was made scalable.…”
Section: Pre-vascularized Moa For Biomanufacturing Organ-scale Tissuesmentioning
confidence: 99%
“…Additionally, Sun et al reported a bioink consisting of densely packed spheroids for chondrogenic differentiation [16]; however, such a strategy requires the careful design of a thermoresponsive poly(N-isopropyl acrylamide) (PNIPAAm) porous hydrogel and fails to provide the necessary extracellular matrix microenvironment for tissue maturation. Furthermore, Ho et al developed an aggregate-based bioink without the addition of any biomaterials, achieving close to physiological cell density [17]; however, the wholly cellular bioink could only be printed in a collagen/Matrigel supporting bath with unsatisfactory shape fidelity. Therefore, the printability of granular spheroids as a generalizable bioink has not been demonstrated, limiting their applications in complex tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%